Cross-Sector Collaboration and Technology: Key to Optimizing Regional Finance for Equitable Development in Indonesia - Desi Wahyuni (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
Local financial management in Indonesia still faces significant challenges, such as budget inefficiencies, high dependence on central funds, and lack of locally generated revenue (PAD), which exacerbates development inequality, especially in underdeveloped regions such as Papua. This research highlights the importance of cross-sector collaboration and technology utilization for the optimization of local finance to achieve sustainable development equity. Collaboration between central and local governments, the private sector, and the community can improve transparency and accountability of budget management, while technologies such as e-budgeting, blockchain, and the Local Government Information System (SIPD) can accelerate the budget planning and monitoring process. This study uses a descriptive qualitative approach with thematic analysis of primary and secondary data to evaluate the effectiveness of technology integration and cross-sector collaboration. The results show that a strong synergy between collaboration and technology can improve budget efficiency, reduce dependency on central funds, and accelerate infrastructure development and public services in disadvantaged areas. Policy recommendations include strengthening local government capacity, implementing a blockchain-based monitoring system, and involving communities in development planning. This research contributes to the local financial management literature by offering evidence-based solutions that support inclusive and equitable development in Indonesia.